Features of charge pairs recombination in the track regions of organic solid scintillators. Part II - Tarasenko, O.A. (Functional Materials, 2013)
In this paper we studied the influence of ionization loss of a heavy charged particle on change in the distance between the charge pairs, which are generated in an organic solid scintillator, and on recombination processes between them. The specific energy loss dE/dx and the ranges of alpha particles and protons were calculated by computer simulation using SRIM-2011 program. The values of a correction factor for the revised calculation of the distance between the charge pairs were obtained. In contrast to the previous studies, we took into account the change of dE/dx-value of a charged particle passing through an organic medium.